Effective field theory for the nucleon-quarkonium interaction - Tarrús Castellà, Jaume; Krein, Gastão [UNESP] (American Physical Society (APS), 2018)
We develop an effective field theory approach for the S-wave quarkonium-nucleon system. We adopt a natural power counting equivalent to Weinberg's power counting in nucleon-nucleon effective field theories and compute the quarkonium-nucleon potential, scattering length and effective range up to O(mπ3/Λχ3) accuracy, including the full light-quark mass dependence. We compare our results with lattice QCD studies of quarkonium-nucleon system, obtain an estimation of the leading order quarkonium-nucleon contact term and determine the J/ψ and ηc chromopolarizabilities.